Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Materials and Colors of Artificial Water Container Toward Mosquito (Aedes Aegypti) Egg Index

Abstract: Aedes aegypti is the main vector of Dengue Haemorrhagic Infection in Indonesia and it is predominantly breeding in clear water within household artificial containers. Thus, it is necessary to implement environmental management that is tends to be simple, low-cost and effective to create disadvantageous condition for Aedes Aegypti mosquito's breeding sites. The objective of this study is to investigate the effect of water container colour made of concrete and plastic material to the amount of Aedes Aegypti egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…aegypti females is primarily based on a greater attraction to dark surfaces [30], suggesting that Ae. aegypti prefer dark breeding areas, over other colours such as blue, yellow, and white [31]. Colton et al [32] reported that Aedes mosquitoes lay the majority of their eggs in black ovitraps, possibly to protect the eggs and offspring from predators, as the eggs are typically black.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti females is primarily based on a greater attraction to dark surfaces [30], suggesting that Ae. aegypti prefer dark breeding areas, over other colours such as blue, yellow, and white [31]. Colton et al [32] reported that Aedes mosquitoes lay the majority of their eggs in black ovitraps, possibly to protect the eggs and offspring from predators, as the eggs are typically black.…”
Section: Discussionmentioning
confidence: 99%